Audiologist's Perspective in Auditory Rehabilitation: Implications for Ethical Conduct and Decision-Making in Portugal - Marques, Tatiana (2022)
Ethical standards in audiology have been continuously improved and discussed, leading to the elaboration of specific regulatory guidelines for the profession. However, in the field of auditory rehabilitation, audiologists are still faced with circumstances that question their ethical principles, usually associated with the support of the hearing aids industry. The study explores the decision-making process and ethical concerns in auditory rehabilitation as they relate to the practice of audiology in Portugal. An online questionnaire constructed by the authors was used and sent to the email addresses of a list of audiologists, registered with the Portuguese Association of Audiologists. The questionnaire was answered by 93 audiologists with clinical experience in auditory rehabilitation for more than one year. The collected data demonstrated that audiometric results and clinical experience are the most important factors for decision-making in auditory rehabilitation practice. Moreover, incentives from the employers or manufacturers were identified as the main cause of ethical dilemmas. This study highlights the ethical concerns regarding the clinical practice of auditory rehabilitation in Portugal, revealing that the decision-making process is complex and, specifically in this field, the current practice may not be adequate for effective compliance with professional ethical standards.